Peace education and its enemies: A view from transitional countries - Spajić-Vrkaš, Vedrana (2003)
The paper focuses on the assets and obstacles to promoting peace education in European transitional societies as an important part of European integration and stabilisation processes. Three issues are discussed in particular : a) conceptual and policy ambiguities at global level in reference to the promotion of peace in general and peace learning/education in particular, b) the evolving of a pan-European consensus about global commitments, and c) special challenges to promoting peace education faced by South East European countries. A special emphasis in the third part is given to the so called 'implementation gap', i.e. the inconsitency between political commitments and policy implementation.